Smad4-deficient T cells promote colitis-associated colon cancer via an IFN-γ-dependent suppression of 15-hydroxyprostaglandin dehydrogenase - Choi, Sung Hee; Huang, Alex Y.; Letterio, John J.; Kim, Byung-Gyu (Frontiers in Immunology, 2022)
Immune cells and the cytokines they produce are important mediators of the transition from colitis to colon cancer, but the mechanisms mediating this disease progression are poorly understood. IFN-gamma is a major cytokine in colitis pathogenesis, but in the context of the disease, considerations have almost exclusively been restricted to its immune-modulatory and epithelial-directed functions. Here we explore whether IFN-gamma influences tumor progression by expanding effector memory T cells (TEM) population and restricting the expression of tumor suppressors in a preclinical model of spontaneous colitis-associated colorectal cancer (CAC). We show that IFN-gamma expression is significantly increased in the T cells and colon of mice with a T cell-restricted deletion of the TGF-β intermediate, SMAD4 (Smad4TKO). An increase of IFN-gamma expression correlates with the onset of spontaneous CAC in Smad4TKO mice by 6 months of age. This phenotype is greatly ameliorated by the introduction of a germline deletion of IFN-gamma in Smad4TKO mice (Smad4TKO/IFN-gKO, DKO). DKO mice had a significantly reduced incidence and progression of CAC, and a decrease in the number of mucosal CD4+ TEM cells, as compared to those of Smad4TKO. Similarly, the colon epithelia of DKO mice exhibited a non-oncogenic signature with a decrease in the expression of iNOS and p-STAT1, and a restoration of the tumor suppressor gene, 15-PGDH. In vitro treatment of human colon cancer cell culture with IFN-gamma decreased the expression of 15-PGDH. Our data suggest that IFN-gamma produced by activated TEM promotes epithelial malignancy by suppressing the expression of tumor suppressor genes.